Analysis of the Management of Incoming Letters at the South Sulawesi Provincial Health Office - Yusra Yusra; Muh. Nasrullah; Muh. Darwis (ASHA Publishing, 2024)
This study aims to find out the analysis of the management of incoming mail at the South Sulawesi Provincial Health Office. This research is qualitative, using data collection techniques through observation, interviews and documentation. The research informants were 3 employees of the South Sulawesi Provincial Health Office. The results of this study show that the management of incoming letters at the South Sulawesi Provincial Health Office is running